Hubungan Motivasi Petani dalam Berusahatani Sayur-mayur dengan Keterlibatannya pada Kegiatan Peken Carik di Subak Sembung, Kelurahan Peguyangan, Kecamatan Denpasar Utara - NI LUH GEDE NIRMALA DEVI; I DEWA GEDE RAKA SARJANA; WAYAN SUDARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Correlation of Farmers Motivation to Cultivate Vegetables with TheirInvolvement atPeken Carik Activity in Subak Sembung, Peguyangan Village,North Denpasar Sub-districtVegetables are one of the horticultural sub-sector plants which is amount cultivatedbylots of farmers, one of them is farmers in Subak Sembung, Peguyangan Village,North Denpasar Sub-district. Subak Sembung developed into an ecotourism and has asupporting program known as peken carik activity. All of farmers in Subak Sembungare involved at peken carik activity and make it as an shopping tour media to sellvegetables to people which is in line with their motivation to cultivate vegetables. Thisresearch aims to determine the level of farmers motivation to cultivate vegetables, thelevel of farmers involvement at peken carik activity, and correlation between thefarmers motivation to cultivate vegetables with their involvement at peken carik activityin Subak Sembung, Peguyangan Village, North Denpasar Sub-district. Sampling are 60respondent using incidental method. The data were analyzed used qualitative analysisand quantitative analysis of Spearman rank correlation test.The result of qualitativeanalysis to describe the level of farmers motivation to cultivate vegetables was in highcategory, however the level of farmers involvement at peken carik activity was in verylow category. The result of Spearman rank correlation test showed the correlation offarmer motivation to cultivate vegetables with their involvement at peken carik activityin Subak Sembung, Peguyangan Village, North Denpasar Sub-districtwas in lowcategory.